A review of the genus Ammoplanellus Gussakovskij (Hymenoptera: Crabronidae: Pemphredoninae) from India with the description of two new species - Rajan, Tessy; Kumar, P. Girish; Sureshan, P.m.; Hegde, V.d. (Zootaxa, 2024)
The Indian species of Ammoplanellus Gussakovskij, 1931 are reviewed and two new species, namely A. keralaensis and A. smithi Tessy, Girish Kumar & Sureshan sp. nov. are described. A key to the species of Ammoplanellus Gussakovskij from the Oriental region is provided.